The taxonomy of Speodromia platyarthrodes (Stebbing, 1905) (Crustacea: Brachyura), an unusual dromiid crab endemic to South Africa - Ng, Peter K. L. (Zootaxa, 2016)
The poorly known dromiid crab Speodromia platyarthrodes (Stebbing, 1905), endemic to South Africa, is redescribed and figured. Speodromia is unique among dromiids in possessing a large cavity on the anterior part of the sub-branchial region, which is believed to be associated with respiration. The systematics of the genus is discussed and is confirmed to be a member of Dromiinae De Haan, 1833, s. str.